Endoscopic Management of Malignant Colonic Obstruction - Seung Young Seo; Sang Wook Kim (Korean Society of Gastrointestinal Endoscopy, 2020)
Advanced colorectal cancer can cause acute colonic obstruction, which is a life-threatening condition that requires emergency bowel decompression. Malignant colonic obstruction has traditionally been treated using emergency surgery, including primary resection or stoma formation. However, relatively high rates of complications, such as anastomosis site leakage, have been considered as major concerns for emergency surgery. Endoscopic management of malignant colonic obstruction using a self-expandable metal stent (SEMS) was introduced 20 years ago and it has been used as a first-line palliative treatment. However, endoscopic treatment of malignant colonic obstruction using SEMSs as a bridge to surgery remains controversial owing to short-term complications and longterm oncological outcomes. In this review, the current status of and recommendations for endoscopic management using SEMSs for malignant colonic obstruction will be discussed.